The collaborative interdependence in the local production arrangement of gems and jewels in South of Brazil. (25th September 2019) - Filho, Luiz Fernando Fritz; Mozzato, Anelise Rebelato; Fritz, Karen Beltrame Becker
This research aims to understand the inter-organisational relations (RIOs) in the local productive arrangement (LPA) of gems and jewels of the South of Brazil, analysing to what extent the prevalence of characteristics of collaborative interdependence occurs. The paper addresses questions about developing LPAs, followed by the centralised discussion on the importance of the presence of collaborative interdependence between the different actors in RIOs. This exploratory research is characterised as a qualitative case study. The data collection was done through interviews, non-participant observation, and documentary analysis. Content analysis was adopted as a data analysis technique. The results indicate the occurrence of collaborative interdependence between the different actors that maintain RIOs. Collaboration on actions related to shared goals, use of common resources and complementarity of tasks is confirmed. However, it is also evidenced that the collaborative interdependence can be more effective, covering the LPA.